Stimulating the Innovative Development of the Regions of the Russian Federation within the Framework of Strategic Investment Projects - E. A. Perminova (Евразийская интеграция: экономика, право, политика, 2022)
The present study is aimed at forming proposals to stimulate accelerated innovative development of the regions of the Russian Federation in the conditions of increasing global crises associated with the influence of the unstable international situation in connection with the events in Ukraine and the introduction, as well as the prospect of sanctions against the Russian Federation, as well as the impact on both the world and the Russian economy of the consequences of significant restrictions due to the situation with coronavirus.Aim. Formation of proposals for accelerated innovative development of the regions of the Russian Federation based on the use of strategic investment projects in the conditions of reconstruction of territorial production complexes, which will form the prerequisites for the advanced development of the regions.Tasks. To consider approaches to stimulating accelerated innovative development of the regions of the Russian Federation and its assessment based on: the use of key performance indicators; diversification of the economic potential of the regions, as well as the use of venture financing; introduction of the concepts of strategic investment projects and strategic investment initiatives into strategic regional development programs; the use of the theory of the territorial-industrial complex in modern economic conditions.Methods. In this paper, using the methods of factorial, statistical and quantitative analysis, proposals have been developed for the formation of measures to achieve maximum success in the innovative development of advanced industries in the regions of the Russian Federation.Results. The study showed that in order to achieve the objectives of accelerated innovative development of the regions of the Russian Federation, when forming strategic planning documents, it is necessary to focus on the main “development complexes”, participation in the implementation of a new model of economic growth based on the prin ciples of public-private partnership based on a comprehensive theoretical and methodological approach to the formation of socio-economic policy and the active use of strategic investment projects.Conclusions. It is advisable in the strategic programs of the regions to determine the creation of hightech innovative projects for processing raw materials available on the territory in order to get out of the dependence of the economy on raw materials; to create the necessary conditions for improving the investment climate in order to attract high-tech projects of leading world states for their further use in their own needs; actively diversify existing own high-tech projects in order to maximize profits and create an image of a highly developed, competitive region; create high-tech divisions on the basis of financial and economic institutions to launch and finance innovative, knowledge-intensive projects with a view to their further diversification and integration both in the region and with third entities.